2015
DOI: 10.13055/ojhmt_6_1_3.150504
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics and Cytogenetics data of 317 patients with de novo acute leukemia

Abstract: Background/Aims: Cytogenetic and molecular genetics play a pivotal role in treatment of acute leukemias. We prospectively evaluated genetic alterations in Brazilian patients with acute myeloid leukemia (AML) or acute lymphoblastic leukemia (ALL) and their association with clinical and laboratorial data. Methods: Flow cytometry, conventional cytogenetics (CC), FISH, PCR, RT-PCR and sequencing were performed on samples from 161 de novo ALL and 155 AML.Results: Main CC findings in AML were t(15;17) (19.4%), +8 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…These findings are in accordance with international literature. 21,22 A study representing the southern region of Pakistan also demonstrated increased frequency of Philadelphia chromosome in the adult ALL. 23 Similar findings were observed in Sudanese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in accordance with international literature. 21,22 A study representing the southern region of Pakistan also demonstrated increased frequency of Philadelphia chromosome in the adult ALL. 23 Similar findings were observed in Sudanese population.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is comparable with Brazilian study carried out by Compos C et al i.e., 45.8%. 21 Hyperdiploidy was the most frequently occurring chromosomal aberration with majority of the cases involving childhood and adolescence. Hyperdiploidy is a prognostically favorable abnormality.…”
Section: Discussionmentioning
confidence: 99%